Developing Information System on Lunar Crescent Observations - T. Hidayat; P. Mahasena; B. Dermawan; D. Herdiwijaya; H. Setyanto; M. Irfan; B. Suhardiman; A. Santoso (Journal of Mathematical and Fundamental Sciences, 2010)
We present a progress report on the development of information system of lunar crescent astronomical observations which will be largely accessible for public domain. This consists of calculations of the Moon's ephemeris as well as systematic real-time lunar crescent observations. A well suited small telescope, equipped with a simple digital detector, is connected to a server to provide information on lunar crescent observations. The system has been used and worked well. The only constraint is poor weather condition. Network of small telescopes, installed at various locations in Indonesia, are currently planned to provide plethora of data. In the long term, this will be used to help to determine the astronomical visibility criteria of lunar crescent for Islamic calendar.